(untitled) (Italian Journal of Public Health, 2011)
Background: The Italian Observatory Healthcare Report (IOHR - 8th edition) [1] aims to help policy makers in the process of decision making through a set of validated indicators resulting from the multidisciplinary activity of several public health experts. Its main task is to gather comparable data on the health status and the quality of health care services throughout the Italian regions. Methods: The report adopts a European approach in order to build a benchmarking activity and the selection criteria of indicators include: meaning, feasibility and quality, comparability and reliability. Each indicator is analyzed by experts in terms of meaning, pattern, validity and limits, graphic representation; recommendations are included for decision makers. A peer reviewing is performed for quality assessment. Results: The IOHR 2010 included 96 indicators, analysed by 203 authors. Through comparable regional data coming from different sources, an overview of the Italian Health System, and a gauging of the impact that different regional organizational and institutional arrangements have on the quality of health services, have been provided. Though data analysis showed a North-South gradient in the quality and the organization of health care services, nevertheless, the overall health status of Italian population is good. Risk factors, lifestyles and prevention together with geographical and social differences in health status and service access are the main priorities. Conclusions: The IOHR helps monitoring the health status in the Italian regions through specific indicators characterized by scientific strictness. It contributes to identifying the situations of excellence and disseminating public health care control tools in order to facilitate the decision making process.